HUBUNGAN SELF CONFIDENCE DENGAN SPEAKING SKILL SISWA KELAS V SEKOLAH DASAR NEGERI KELURAHAN KEBON JERUK - Anida Aulia Albarashwa Puteri; Nidya Chandra Muji Utami; Yofita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between self-confidence and speaking skill in fifth grade elementary school students. The research used quantitative method with correlational approach. Data collection was done with a questionnaire to measure students' self-confidence and a speaking test with a type of responsive test, namely a simple question and answer test to measure students' speaking skills. The number of samples in this study were 90 students. Data analysis techniques used are normality test, homogeneity test, linearity test, and hypothesis testing in the form of correlation coefficient test. The results of this study indicate a significant positive relationship between the self confidence variable and the speaking skill variable with a correlation coefficient value of 0.408 which is included in the medium category and a significance value of 0.000 <0.05, so it can be concluded that H0 is rejected and H1 is accepted. This shows that the higher the students' self-confidence, the higher the speaking skill.